ADAD1 and ADAD2, testis-specific adenosine deaminase domain-containing proteins, are required for male fertility - Elizabeth Snyder (Nature Portfolio, 2020)
Abstract Adenosine-to-inosine RNA editing, a fundamental RNA modification, is regulated by adenosine deaminase (AD) domain containing proteins. Within the testis, RNA editing is catalyzed by ADARB1 and is regulated in a cell-type dependent manner. This study examined the role of two testis-specific AD domain proteins, ADAD1 and ADAD2, on testis RNA editing and male germ cell differentiation. ADAD1, previously shown to localize to round spermatids, and ADAD2 had distinct localization patterns with ADAD2 expressed predominantly in mid- to late-pachytene spermatocytes suggesting a role for both in meiotic and post-meiotic germ cell RNA editing. AD domain analysis showed the AD domain of both ADADs was likely catalytically inactive, similar to known negative regulators of RNA editing. To assess the impact of Adad mutation on male germ cell RNA editing, CRISPR-induced alleles of each were generated in mouse. Mutation of either Adad resulted in complete male sterility with Adad1 mutants displaying severe teratospermia and Adad2 mutant germ cells unable to progress beyond round spermatid. However, mutation of neither Adad1 nor Adad2 impacted RNA editing efficiency or site selection. Taken together, these results demonstrate ADAD1 and ADAD2 are essential regulators of male germ cell differentiation with molecular functions unrelated to A-to-I RNA editing.